Higher Incidence of Congenital Aortic Valve Stenosis in Higher Magnetic Latitude Countries: New Insights and Potential Therapies - Alabdulgader, Abdullah (Archives of Clinical and Biomedical Research, 2025)
Bicuspid aortic valve stenosis (BCAS) is the most prevalent congenital heart defect (CHD), with a global incidence of 3–4%, whereas all other subtypes collectively account for only 1% of live births. BCAS represents a severe form of valvular aortic stenosis (VAS) in adulthood, characterized by progressive pathological changes that cannot be attributed solely to hemodynamic stress, implicating intrinsic abnormalities in bicuspid valve tissue. Given the stagnation in aortic stenosis therapeutic advancements, a comprehensive CHD risk factor study analyzed over three million statistical variables from 7,327 questionnaires encompassing 412 potential genetic, physiological, medical, and environmental risk factors. The analysis of our results and other international studies revealed a progressive increase in BCAS incidence with latitude, suggesting an epigenetic influence of the planetary electromagnetic field on endothelial–mesenchymal transformation (EndoMT), thereby supporting the auroral polar paradox effect in aortic valve morphogenesis. This finding underscores the necessity of elucidating the cellular and molecular mechanisms governing EndoMT in congenital and acquired heart disease pathogenesis. The potential to manipulate EndoMT and its regulatory pathways through targeted external electromagnetic modulation emerges as a promising paradigm shift, offering novel therapeutic strategies to reverse or mitigate BCAS and other cardiovascular malformations, thereby advancing the frontier of regenerative cardiology and congenital heart disease interventions.